A comparison of an effect of different anti-inflammatory drugs on human platelets. Issue 6 (September 1970) - O'Brien, J. R.; Finch, Wendy; Clark, Elizabeth
Abstract : Different doses of aspirin, indomethacin, paracetamol, benorylate, and sodium salicylate were taken by four volunteers. The minimal dose that altered a platelet function test and the persistence of this alteration at different dose levels were studied. Minute doses of indomethacin (0·035 mg/kg) were effective but the effect of even a large single dose did not persist. A tenth of the therapeutic dose of aspirin (1 mg/kg) was effective, and higher doses altered the platelets' function for several days. Benorylate in a high therapeutic dose gave aspirin-like results. Paracetamol and sodium salicylate were relatively inactive. The persistence of the aspirin effect may be related to the acetyl group. These findings are surveyed in relation to a general theory of the action of anti-inflammatory drugs.